Des Moines Water Works: Collaborating to Restore and Protect Source Water. Issue 2 (6th March 2023) - Corrigan, Ted; Terry, Jennifer
Key Takeaways: Des Moines Water Works' (DMWW's) source water faces significant water quality challenges from decades of agricultural nutrient pollution in Iowa. Lackluster results in regulating nutrient pollution, along with population growth and effects of climate change, add urgency to DMWW's drive to improve source water quality. To protect its source water, DMWW has collaborated with groups outside of its typical scope, building relationships with those who have the same values and vision.